Creep behavior of boom clay. (June 2015) - Yu, H.D.; Chen, W.Z.; Gong, Z.; Tan, X.J.; Ma, Y.S.; Li, X.L.; Sillen, X.
Abstract: Several creep tests (lasting more than one year) were performed to study the delayed mechanical behavior of Boom clay under the hydro-mechanical coupling effect. To prevent the soil from swelling as much as possible during re-saturation, the samples were submitted to a confining pressure close to the in situ effective mean stress (2.5 MPa) at a room temperature of 21 °C. However, certain swelling still exists at the beginning of the saturation. Creep tests further highlight the creep potential of Boom clay. Delayed behavior became more and more significant as the deviatoric stress increased. A deviatoric stress threshold (approximately 1.0 MPa), below which only primary creep occurred, was proved to exist from the development of secondary and tertiary creep phases during the creep tests. If we introduce a quasi-steady state creep rate, i.e., the average creep rate after the creep deformation becoming stable, it can be found that the quasi-steady state creep rate of Boom clay is on the order of 10 −6   ε /h under low deviatoric stress (1.5 MPa) in the laboratory, which is on the same order as the average creep rate of the in situ measurements in the second year (1988). However, in situ measurements show that steady creep state of the host rock was not reached even after five years. The in situ quasi-steady state diameter reduction rate calculated from the average of 10 years (1996–2006) of stable deformation of the tunnel linings is on the order of 10 −8   ε /h. Highlights: Test results further highlight the creep potential of Boom clay. Certain swelling still exists during saturation under the in situ effective stress. A deviatoric stress threshold was proven to exist during the creep tests. The quasi-steady state creep rate measured in lab is consistent with in situ measurements.